Geriatric depression in Quechua-speaking high-altitude communities in Ayacucho, Peru, in 2023 - Arias-Aroni, Gianella Alejandra (2025)
Objective: To determine the association between depression and the domains of geriatric assessment. Materials and methods: A cross-sectional analytic study was conducted in five highland communities from Ayacucho, Peru. Trained personnel administered structured questionnaires, including the Geriatric Depression Scale (GDS), Pfeiffer Short Portable Mental Status Questionnaire (SPMSQ), Katz Index of Independence in Activities of Daily Living, and Abbreviated and modified Gijon's social-familial evaluation scale (SFES). Sociodemographic information and blood oxygen saturation were collected from among ≥60 years population members (n = 156). For bivariate analysis, Fisher's exact and chi-square tests were used. Bivariate and multivariate Poisson regression with 95% CI were also administered to explore the association of geriatric depression with sociodemographic information, blood oxygen levels and social, functional, and mental spheres of geriatric assessment. Results: More than half of the participants were female (52.6%). Mean age was 72.45 (±7.90) years. The majority were married (66.7%), had no schooling (54.5%), and were dedicated to agricultural work (51.3%). Prevalence of probable depression was 53.2%. Having a moderate or severe cognitive impairment (aPR = 1.33) was a risk factor for the occurrence of probable depression, while having a living companion (aPR = 0.67) and coming from Chuschi (aPR = 0.39) were protective factors. Conclusion: Probable depression in the elderly was highly prevalent in this Quechua-speaking region of the Peruvian highlands and was associated to cognitive impairment.